2013
DOI: 10.1371/journal.pone.0060794
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between C3 Plant Foliar Carbon Isotope Composition and Element Contents of Grassland Species at High Altitudes on the Qinghai-Tibet Plateau, China

Abstract: Relationships of foliar carbon isotope composition (d 13 C) with foliar C, N, P, K, Ca, Mg contents and their ratios of 219 C 3 species leaf samples, obtained in August in 2004 to 2007 from 82 high altitude grassland sites on the Qinghai-Tibet Plateau China, were examined. This was done with reference to the proposition that foliar d 13 C increases with altitude and separately for the life-form groups of graminoids, forbs and shrubs and for the genera Stipa and Kobresia. For all samples, foliar d13 C was negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 54 publications
6
23
0
Order By: Relevance
“…Generally, C was negatively correlated with ash or mineral content (Zhou et al 2013). Thus, positive correlation between d 13 C and C was expected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, C was negatively correlated with ash or mineral content (Zhou et al 2013). Thus, positive correlation between d 13 C and C was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Pinus tabulaeformis is negatively related to N. Negative relationships between d 13 C and K were reported for Quercus aquifolioides (Li et al 2009), Pinus tabulaeformis (Li et al 2011), sugar beet (Tsialtas and Maslaris 2006), and grassland species on QinghaiTibet Plateau (Zhou et al 2013). However, while Cao et al (2009) and Zhao et al (2007) found negative relationships between d 13 C and K for Tamarix ramosissima, Artemisia ordosica, and Hedysarum scoparium, as well, they also found positive relationships for Populus euphratica and Caragana korshinskii.…”
Section: Ofmentioning
confidence: 94%
See 3 more Smart Citations